Enforcing "Equal Pay for Equal Work" in the EU: What would it take? - Silvia De Poli; Sofia Maier (European Commission, Joint Research Centre (JRC), 2022)
The European Parliament has recently approved new binding pay transparency measures to promote ''Equal Pay for Equal Work'', an EU founding principle which is at the heart of the European Pillar of Social Rights Action Plan towards 2030. Using harmonized microdata for the EU 27 countries and a novel estimation approach -based on blocking with regression adjustments- we provide new comparable estimates of the gap in gross hourly wages between women and men performing similar work. This gap ranges from about 6% in Germany to 18% in Estonia. We also shed new light on the (heterogeneous) distributional consequences of a hypothetical enforcement of equal pay for equal work, simulating an upward shift in women's gross hourly wage. The strongest impact on the distribution of labour earnings would take place in countries with high gender pay gaps for equal work and small gender gaps in employment and hours worked (mainly Central and Eastern European countries), whereas only marginal effects are identified in countries with large gaps in hours worked and gender segregation in the type of work done (Western European countries), and also in countries with large employment gaps (Southern European countries). We also identify income poverty-reducing and inequality-increasing effects. The latter is driven by a composition effect (under-representation of employed women in low-income households), which is only partly offset by the tax-benefit system.
Keywords: J01; J24; J38; D63; J78; 330; gender pay gap; pay transparency; regression-after-blocking; inequality; European Union